Ways to Reduce Losses in Power Transformers - Qurbonov Nurali Abdullayevich; Qurbonova Munisaxon Sanjar qizi; Tog’ayev Axror Ikrom o’g’li (Zien Journals, 2023)
Research in the field of transformer engineering has led to the creation of transformers with reduced no-load losses, which makes it possible to reduce the overall level of losses in distribution networks
Keywords: transformer; calculating electricity losses; the efficiency